Ethno-ECLIPSE learning model: The bridge between collaboration and critical thinking skills - Panggih Priyambodo; Paidi Paidi; Insih Wilujeng; Asri Widowati (Journal of Education and Learning (EduLearn), 2023)
Collaboration skills and critical thinking skills are two real-life competencies in the 21st century. These two skills are believed to be related to one another. However, research on the magnitude of the correlation between the two skills is rarely investigated. Empowerment of these two skills cannot be separated from the learning model. This study analyzes the relationship between collaboration and critical thinking skills through the ethno-ECLIPSE learning model and conventional learning. This correlation study involved 240 biology students from various universities in Special Region of Yogyakarta and Central Java Provinces, Indonesia. Collaboration skills data was obtained through peer-to-peer rating scales, while critical thinking skills data was collected through essay tests. Data was analyzed by using simple linear regression. The research results showed collaboration skills significantly correlate with students’ critical thinking skills. The contribution of collaboration to critical thinking skills is higher when applying the ethno-ECLIPSE learning model (86.9%) than in conventional learning (48.2%). Then, the regression equation formed from both learning is parallel but not coincident. The ethno-ECLIPSE learning model can be the right choice and is highly recommended for achieving learning goals, especially increasing collaboration and critical thinking skills of pre-service teacher.